A VALIDATED RP-UPLC METHOD DEVELOPMENT FOR SIMULTANEOUS ESTIMATION OF LANSOPRAZOLE AND NAPROXEN IN BULK AND TABLET DOSAGE FORM - Singh, Sunil; Choudhary, Nisha; Rai, Jyoti; Siddiqui, Inamullah; Sharma, Surabhi (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Objective:Â A simple and precise RP-UPLC method development and validation for simultaneous estimation of lansoprazole (LAN) and naproxen (NAP) in bulk and tablet Dosage Form. Method: Simple, accurate and cost efficient RP-UPLC method has been developed and validated for the simultaneous estimation of lansoprazole and naproxen in bulk and tablet dosage form.Â The optimum conditions for the analysis of the drug were established. Results: The retention time (RT) was found to be 3.905 and 2.650 min for lansoprazole (LAN) and naproxen (NAP), for analysis the maximum wavelength (Î»max) was found 284nm for simultaneous estimation of LAN and NAP. The method was linear and found to be range between 5-30 Î¼g/ml (r2= 0.998) and 10-35 Î¼g/ml (r2= 0.999) for LAN and NAP respectively. The value of limit of detection and limit of quantification was 0.8397 and 2.979 Î¼g/ml for LAN and 0.4678 and 1.5593 Î¼g/ml for NAP, the recovery was found between 80,100 and 120% and RSD less than 2 for LAN and NAP. The method was satisfactorily validated as per the ICH guideline. Conclusion: The proposed methods were simple, sensitive, precise, accurate, reproducible, quick and useful for routine quality control. This study shows that the proposed RP-UPLC method is useful for the routine determination of LAN and NAP in its bulk and tablet dosage form. Keywords: Lansoprazole, Naproxen, RP-UPLC, Method validation and TabletsÂ